METHODS OF TEACHING RUSSIAN AS A FOREIGN LANGUAGE AT THE STAGE OF PRE-UNIVERSITY TRAINING - Kurbanova Zulfiya Asrarovna (Journals Park Publishing, 2023)
This article discusses the methodology of teaching the Russian language in higher educational institutions and the issues of learning Russian as a foreign language in preparation for higher educational institutions.
Keywords: Forms of lessons, standard of education, foreign languages, Russian alphabet, language skills, monotony of lessons, abstract thinking.